the impact of intermittent training-strength-medium on the change of direction speed and explosive force of the lower extremities in football players under the age of 17 - صادو محمد أمين; بوحاج مزيان (sports creativity, 2025)
This study aims to know the effect of intermittent training-strength-medium on the change of direction speed and the explosive force of the lower extremities of football players, and for this purpose we used the experimental method on a sample of 20 players from the JSD U17 team, It was chosen deliberately, as the 20m zigzag test and SJ test were used as tools for the study, it was concluded that intermittent training- strength-medium positively affects the speed of change direction and the explosive force of the lower extremities, and on this basis the researcher recommends the necessity of The use of intermittent-strength-medium training in training programs and keenness to improve the speed of change of direction and explosive power in football players under the age of 17